Role of the Autonomic Nervous System in the Tumor Micro-Environment and its Therapeutic Potential - Xu, Zhifang; Shioda, Seiji; Masahisa, Jinushi; Kawakami, Yutaka; Ohtaki, Hirokazu; Calista Lim, Huimin; Wang, Shenjun; Zhao, Xue; Liu, Yangyang; Zhou, Dan; Guo, Yi (Current Pharmaceutical Design, 2017)
Although evidence over the last 30 years suggests that the autonomic nervous system (ANS) mediates stress-induced allostatic and immune responses, the crucial role that it plays in the tumor micro-environment has only recently been reported. Here, we review the action of ANS signaling in this micro-environment. Emerging data suggest that primary tumors are innervated by the ANS which mediates stress-related effects on tumor progression. The activation of the sympathetic nervous system (SNS) takes advantage of neurotransmitters and neuropeptides from the innervating neural circuitry and/or hypothalamic-pituitary-adrenal axis glucocorticoids via their receptors to modulate the gene expression associated with oncogenesis, the proliferation and apoptosis of tumor cells, angiogenesis, and the tumor-associated immune response. The parasympathetic nervous system has also been implicated in some tumor types, but its contribution in the tumor micro-environment remains unclear. In addition to identifying the ANS signaling pathways involved in tumor progression, recent reports suggest that the ANS could be a potential biomarker to predict tumor progression, and have identified new pharmacological strategies, such as the use of β-adrenergic blockers, to inhibit tumor progression and metastasis by targeting this system. These findings are reviewed here.
Keywords: Autonomic nervous system